PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN BUAH TOMAT (Solanum lycopersium) DALAM UPAYA PENCEGAHAN RESIKO PENYUMBATAN PEMBULUH DARAH DI RW 16, KELURAHAN CIPAGERAN, KECAMATAN CIMAHI UTARA - Noviar, Ganjar; Hayati, Eem; Ramadhani, Riski Nur; Nurhayati, Betty (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
In hypertensive patients, platelet hyperaggregation occurs. Platelet hyperaggregation will have a bad outcome in acute infarction stroke, in the form of death or neurologic deficits. One plant species that can play a role in preventing hyperaggregation complications is tomato fruit (Solanum lycopersicum) which is a horticultural plant cultivated in Indonesia. The compound content in Tomato Fruit (Solanum lycopersicum) includes solanine (0.007%), saponin, folic acid, malic acid, citric acid, bioflavonoids (including lycopene, α, and ß-carotene), protein, fat, vitamins, minerals, and histamine which function as antiaggregation. This research uses 2 methods, namely survey and sampling methods to determine the scope of empowerment and education in the form of counseling and mentoring. Apart from that, another method used is an educational method in the form of counseling and assistance to provide an understanding of the use of tomatoes to prevent the risk of blood vessel blockages. The results of the research were 20 cadres with a presentation increase of 51.67%, while the results from 20 residents had a presentation increase of 75.06%. Wilcoxon test results with p value (Sig) < 0.05. This shows that there is a significant difference in scores between the pre-test scores and the post-test scores of cadres and residents of RW. 16, Cipageran Village, North Cimahi District, Cimahi City.